STRATEGIC INNOVATION: THE ROLE OF CREATIVITY AND STRATEGIC PLANNING IN THE COMPETITIVE SUSTAINABILITY OF COMPANIES - Antônio Scapini, Lucas (Revista Gênero e Interdisciplinaridade, 2025)
This study investigates the insertion of an innovative culture in the administrative strategies of contemporary companies, with the objective of elucidating how organizations can integrate innovative practices to ensure competitiveness and sustainability. The current context is marked by rapid technological transformations, social responsibility pressures and constant adaptation demands, making innovation an essential strategic differentiator. The relevance of the theme is the need for companies to align their values, processes and objectives with creativity and experimentation, promoting a positive impact on the market and society. The adopted methodology was qualitative, based on conceptual analysis and practical examples that demonstrate as visionary leadership, interdepportal collaboration and use of technologies can foster innovation. The results indicate that the adoption of an innovative culture requires continuous commitment, investment in training and integration of sustainable practices. When implemented in a structured way, this approach allows organizations to anticipate trends, quickly respond to changes, and consolidate their competitive position. It is concluded that innovation must be seen as an indispensable strategic pillar for long-term organizational success.